Enhancing Students' English Pronunciation With Cake Game Application - febriani, indriani; Sari, Puspa; Syahrir, Syahrir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
In this research, researchers make pronunciation and application the focus of research to improve students' ability to learn pronunciation. This research uses an experimental method with a quasi-experimental design. Participants in this study were divided into two groups, namely the control group and the experimental group. Based on the processing of data, improving the pronunciation ability of this cake game application has a positive impact on improving the ability of English pronunciation in students.